A Critical Analysis of Current World Population Studies - Carles Soriano Clemente (World Review of Political Economy)
Current demographic studies are based on the Malthusian principle of population, which makes a direct extrapolation of the natural law of population of the animal kingdom to the human system. This is in contrast to Marx’s understanding of population, for whom population is determined by historical laws of social production superimposed on biological laws. Analysis of the neo-Malthusian studies on population shows that they are merely quantitative and phenomenological, fail to understand population phenomena, and end up being tautological and functional to the capitalist system. A Marxist view of population based on dialectics and materialism, explains the evolution of population throughout human history and during capitalism. Such analysis allows us to understand the current decline in the rate of population growth and the expected decline in the world population as indicators of the terminal crisis of the social production system based on the reproduction of capital through commodity production and labor exploitation.